Problem Based Learning and Deep Learning Approach Effects on Student Learning Outcomes - Julia Julia; Sigit Ristanto; Affandi Faisal Kuriawan; Nur Khoiri (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of Problem Based Learning (PBL) model assisted by PhET Simulation with Deep Learning approach on student learning outcomes on dynamic fluid topic. The research used a quantitative approach with a quasi-experimental design. The subjects consisted of two XI classes in one of the randomly selected high schools in Semarang. The experimental class used the PBL model combined with PhET simulation to fill in the Learner Worksheet (LKPD) related to the discharge and continuity equations, while the control class did not use PhET and did not fill in the LKPD. Both classes were then given a learning outcome test. The results of the analysis using the Mann-Whitney test showed a significant difference between the learning outcomes of the two classes (U = .000, Z = -5.737, p < 0.001), with the experimental class scoring higher (M = 80) than the control class (M = 19). These findings show that the PBL model assisted by PhET Simulation and a deep learning approach improved student learning outcomes. The conclusion of this study is that the application of PBL model assisted by PhET Simulation and Deep Learning approach effectively improves student learning outcomes on dynamic fluid topic.